738. Role of Respiratory Syncytial Virus and Mycoplasma pneumoniae in Pediatric Community-Acquired Lower Respiratory Tract Infections. (26th November 2018) - Kumar, Sanchit; Chakravarti, Anita; Kumar, Surinder; Kapoor, Seema
Abstract: Background: Respiratory syncytial virus (RSV) infection is a major cause of serious lower respiratory disease in infancy and early childhood and Mycoplasma pneumoniae ( M. pneumoniae ) is a common cause of respiratory tract infections in all age groups. This study was conducted to determine the role of RSV and M. pneumoniae and in pediatric lower respiratory tract infections employing serological tests, polymerase chain reaction (PCR) and reverse transcriptase PCR analysis. Methods: In this prospective study, 75 children aged 1 month to 5 years with acute lower respiratory tract infections (LRTIs) were investigated. Paired serum samples were obtained on admission and after 4–6 weeks to assay for M. pneumonia antibodies. Nasopharyngeal aspirates were obtained for the detection of RSV antigen by using the immunochromatographic test, reverse transcriptase-polymerase chain reaction (RT-PCR) for RSV and M. pneumoniae by PCR. Results: RSV infection was positive in 20(60.60%) children aged <1 year and 13 (39.40%) aged 2–5 years, the difference being statistically insignificant ( P = 0.360). M. pneumoniae infection was documented in a 15(57.6%) children aged <1 year age and 11(42.4%) in age 2–5 years which was statistically significant( P = 0.026). Clinical and radiological features among RSV and M. pnemoniae positive and negative cases were comparable. Thirty (40%) children were positive for RSV antigen and by RT-PCR and 3(12%) only by RT-PCR. S erological evidence of M pneumoniae infection was documented in 24(32%) children . M. pnemoniae PCR was positive in 8 (10.66%) patients. Together, serology and PCR detected M. pneumoniae in 26(34.66%) children. Considering RT-PCR as a diagnostic standard, the sensitivity of RSV antigen by immunochromatography was 90.90%, specificity 100%, positive predictive value 100% and a negative predictive value of 93.3%.The sensitivity of M. pneumoniae serology was 75%, specificity 73.3%, positive predictive value 25% and a negative predictive value of 96% considering PCR as a diagnostic standard, . Conclusion: Our data underline the role of RSV and M. pneumoniae as the major cause of community-acquired lower respiratory tract infections in children aged <5 years. Disclosures: All authors: No reported disclosures.